2002
DOI: 10.1097/00000542-200212000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Preconditioning by Isoflurane in Rabbits: A Direct Role for Reactive Oxygen Species

Abstract: Background: Reactive oxygen species (ROS) contribute to myocardial protection during ischemic preconditioning, but the role of the ROS in protection against ischemic injury produced by volatile anesthetics has only recently been explored. We tested the hypothesis that ROS mediate isoflurane-induced preconditioning in vivo.Methods: Pentobarbital-anesthetized rabbits were instrumented for measurement of hemodynamics and were subjected to a 30 min coronary artery occlusion followed by 3 h reperfusion. Rabbits wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(74 citation statements)
references
References 34 publications
3
70
0
1
Order By: Relevance
“…Administration of K ATP channel blocker before isoflurane administration completely blocked the cardioprotection (Tanaka et al, 2003). Isoflurane preconditioning may act via release of small quantities of free radicals to protect myocardium against infarction in rabbits (Mullenheim et al, 2002;Tanaka et al, 2002). Radicals are released from the mitochondria as a consequence of K ATP channel opening (Duranteau et al, 1998;Kowaltowski et al, 2001;McPherson and Yao, 2001a).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of K ATP channel blocker before isoflurane administration completely blocked the cardioprotection (Tanaka et al, 2003). Isoflurane preconditioning may act via release of small quantities of free radicals to protect myocardium against infarction in rabbits (Mullenheim et al, 2002;Tanaka et al, 2002). Radicals are released from the mitochondria as a consequence of K ATP channel opening (Duranteau et al, 1998;Kowaltowski et al, 2001;McPherson and Yao, 2001a).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Preckel et al, 15 isoflurane had no effect on infarct size when administered only during the initial perfusion period. However, inhaled isoflurane has been shown to reduce infarct size in the acute memory phase in rats, 16 rabbits, 17 and dogs 18 when discontinued 15-30 min before LAD occlusion. We 4 and others 3 have previously demonstrated that emulsified isoflurane produces cardioprotection.…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism would be their ability to reduce neuronal excitability through enhanced inhibitory and depressed excitatory synaptic transmission (101)(102)(103). It has been reported that small bursts of ROS production may initiate preconditioning in the myocardium (104,105), and that isoflurane induced such a ROS production by inhibiting the respiratory chain in myocardial mitochondria (106). VA may also precondition brain against ischemia by activating mito K ATP (107,108 -uptake (37,110), and thus prevent the activation of necrotic and apoptotic pathways or attenuate the oxidative stress (111).…”
Section: Volatile Anaesthetics and Clinical Implicationsmentioning
confidence: 99%